EFFECT OF RADIATION EXPOSURE FROM X-RAY MACHINES AND METAL DETECTORS ON THE HEALTH OF SAFETY OFFICERS OF CORRUPTION INSTITUTIONS - Lauditta Indahdewi; Rizki Dinanda (Polteknik Ilmu Pemasyarakatan, 2020)
Health and safety environtment are an important issue and must be materialized in every task execution. As an officer at the forefront of correctional institutions, P2U officers often do not know the magnitude of the impact of radiation exposure to their health. The impact often can be minimized by given the knowledge to the officers P2U related dangers that can cause health problems for them. Therefore, in this study conducted case study on the magnitude of the dose radiation exposure officers who can provide a prudent effect in carrying out the task through laboratory tests. This research can provide knowledge not only to the officers, but also the community that will later visit the Correctional Institution. According to the data listed in the correctional Database system until March 2020 it has been recorded as many as 9,917 guards who every day were on the machine that had a negative impact on their health. With this research, officers need to implement strict protocols in order to avoid the adverse effects of radiation on their health.